2016
DOI: 10.1007/s12026-016-8800-3
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2-targeted fusion antibody improved NK cell-mediated immunosurveillance against K562 cells

Abstract: MHC class I polypeptide-related sequence A (MICA), which is normally expressed on cancer cells, activates NK cells via NK group 2-member D pathway. However, some cancer cells escape NK-mediated immune surveillance by shedding membrane MICA causing immune suppression. To address this issue, we designed an antibody-MICA fusion targeting tumor-specific antigen (vascular endothelial growth factor receptor 2, VEGFR2) based on our patented antibody (mAb04) against VEGFR2. In vitro results demonstrate that the fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The upregulated expression of PD-L1 was not associated with EGFR/STAT3 signaling pathway, but may be affected by EGFR/PI3K/AKT, EGFR/RAS/RAF/ERK, and EGR/PLC-γ signaling pathways [60]. VEGFR2-targeted fusion antibody improved NK cell-mediated immunosurveillance against K562 cells through increasing degranulation and cytokine production of NK cells [61].…”
Section: Effective Immunocyte Exclusion and Dysfunctionmentioning
confidence: 99%
“…The upregulated expression of PD-L1 was not associated with EGFR/STAT3 signaling pathway, but may be affected by EGFR/PI3K/AKT, EGFR/RAS/RAF/ERK, and EGR/PLC-γ signaling pathways [60]. VEGFR2-targeted fusion antibody improved NK cell-mediated immunosurveillance against K562 cells through increasing degranulation and cytokine production of NK cells [61].…”
Section: Effective Immunocyte Exclusion and Dysfunctionmentioning
confidence: 99%
“…Our earlier studies had shown that anti-VEGFR2 exhibits an antitumor effect in breast cancer and leukemia. 29,30 We now extend these studies and show that anti-VEGFR2-IFNa2 (JZA01) has therapeutic efficacy both in vivo and in vitro against metastatic colorectal cancer.…”
Section: Introductionmentioning
confidence: 74%
“…Angiogenesis is critical for tumor growth and metastasis. VEGF/VEGFR signaling plays an important role in tumor growth, progression, metastasis, angiogenesis, and in tumor microenvironment, including immunosuppression (6,(16)(17)(18)(19)(20). Anti-angiogenic therapy targeting VEGF/VEGFR could transform the TME into an immunological favorable state, also described as a "hot" microenvironment.…”
Section: Discussionmentioning
confidence: 99%